Patterns of within-host spread of Chlamydia trachomatis between vagina, endocervix and rectum revealed by comparative genomic analysis - Joseph, Sandeep J.; Bommana, Sankhya; Ziklo, Noa; Kama, Mike; Dean, Deborah; Read, Timothy D. (Frontiers in Microbiology, 2023)
Introduction Chlamydia trachomatis, a gram-negative obligate intracellular bacterium, commonly causes sexually transmitted infections (STIs). Little is known about C. trachomatis transmission within the host, which is important for understanding disease epidemiology and progression. Methods We used RNA-bait enrichment and whole-genome sequencing to compare rectal, vaginal and endocervical samples collected at the same time from 26 study participants who attended Fijian Ministry of Health and Medical Services clinics and tested positive for C. trachomatis at each anatomic site. Results The 78 C. trachomatis genomes from participants resolved into two major clades of the C. trachomatis phylogeny (the “prevalent urogenital and anorectal” clade and “non-prevalent urogenital and anorectal” clade). For 21 participants, genome sequences were almost identical in each anatomic site. For the other five participants, two distinct C. trachomatis strains were present in different sites; in two cases, the vaginal sample was a mixture of strains. Discussion The absence of large numbers of fixed SNPs between C. trachomatis genomes within many of the participants could indicate recent acquisition of infection prior to the clinic visit without sufficient time to accumulate significant genetic variation in different body sites. This model suggests that many C. trachomatis infections may be resolved relatively quickly in the Fijian population, possibly reflecting common prescription or over-the-counter antibiotics usage.